Neue empirische Befunde zur Preissetzung und zum Verbraucherverhalten im Lebensmitteleinzelhandel - Roland Herrmann; Anke Mos̈er; Elke Werner (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2002)
– New Empirical Evidence on Price Setting and Consumer Behaviour in the Retailing Sector. There are two objectives of this article: (i) It is discussed theoretically how the dynamics of pricing decisions of multiproduct retailers can be explained. (ii) It is analyzed empirically by use of scanner data how prices are actually set and how consumers react at the point of sale to price changes and promotional activities by retailers. The empirical evidence focuses on breakfast products in general and jam and breakfast cereals in particular. Main results are the following: 1. Theory of optimal pricing by multiproduct firms suggests that direct and cross price elasticities of demand and marginal costs determine the profit-maximizing price at one point of time. Good reasons do exist additionally for multiproduct retailers to vary prices intertemporally. Sales, e.g., can be consistent with optimal intertemporal pricing. 2. Scanner data for German food retailers in the period September 1996 - June 1999 are utilized in the empirical analysis. The law of one price does not hold for individual branded foods across store types. Price dispersion varies by product. The impact of sales is high in grocery retailing; on average for 20 food categories, one product of a category was on sale every other week. 3. Promotional activities affect demand for branded products strongly, but impacts on quantities varied widely. They were above average for coffee, a storeable product, below average for fresh milk, a less storeable good. In some cases, these effects are so strong that consumers seem to buy the brand only when it is on sale. 4. In the special case of jam, prices are lowest in discounters and highest in supermarkets. The spread of prices is also lowest in discounters and highest in supermarkets. Price-elastic reactions at the point of sale was, however, a uniform pattern across all store types of grocery retailing. The strongest reaction was found in supermarkets with a price elasticity of demand of -5.09.5. For breakfast cereals, strong reactions by consumers occur to various promotional activities. Impacts on demand were, e.g., as high as 175 % when the instruments sales, display and leaflet were combined. Sales were an important feature of promotional activities with a strong demand-increasing effect. Summing up, it can be concluded that an active price policy of grocery retailers is a crucial component of their marketing mix. This is compatible with the finding of a strong price responsiveness of consumers. The stylized fact that the price elasticity of food demand is absolutely low, may be correct for aggregate demand but is not confirmed at the store level. On the contrary: High absolute levels of the store-level price elasticity of demand are typical for branded foods.
Keywords: 330; Lebensmittelpreis; Lebensmitteleinzelhandel; Preismanagement; Sonderangebot; Konsumentenverhalten; Preiselastizität; Markt; Frühstückszerealien; Markt; Deutschland; Konfitüre